A cocoa peptide protects Caenorhabditis elegans from oxidative stress and β-amyloid peptide toxicity. - Patricia Martorell (Public Library of Science (PLoS), 2013)
Background Cocoa and cocoa-based products contain different compounds with beneficial properties for human health. Polyphenols are the most frequently studied, and display antioxidant properties. Moreover, protein content is a very interesting source of antioxidant bioactive peptides, which can be used therapeutically for the prevention of age-related diseases. Methodology/principal findings A bioactive peptide, 13L (DNYDNSAGKWWVT), was obtained from a hydrolyzed cocoa by-product by chromatography. The in vitro inhibition of prolyl endopeptidase (PEP) was used as screening method to select the suitable fraction for peptide identification. Functional analysis of 13L peptide was achieved using the transgenic Caenorhabditis elegans strain CL4176 expressing the human Aβ₁₋₄₂ peptide as a pre-clinical in vivo model for Alzheimer's disease. Among the peptides isolated, peptide 13L (1 µg/mL) showed the highest antioxidant activity (P≤0.001) in the wild-type strain (N2). Furthermore, 13L produced a significant delay in body paralysis in strain CL4176, especially in the 24-47 h period after Aβ₁₋₄₂ peptide induction (P≤0.0001). This observation is in accordance with the reduction of Aβ deposits in CL4176 by western blot. Finally, transcriptomic analysis in wild-type nematodes treated with 13L revealed modulation of the proteosomal and synaptic functions as the main metabolic targets of the peptide. Conclusions/significance These findings suggest that the cocoa 13L peptide has antioxidant activity and may reduce Aβ deposition in a C. elegans model of Alzheimer's disease; and therefore has a putative therapeutic potential for prevention of age-related diseases. Further studies in murine models and humans will be essential to analyze the effectiveness of the 13L peptide in higher animals.